Nurses’ knowledge-attitude-practice of the importance of quality control of nursing documents and the influence of intensive training: a study from a tertiary hospital in China - Li Zhang; Ren-hua Chen; Xue-min Zhong; Meng-yi Xu; Yi-ning Sun; Qian Yao (BMC Medical Education)
Abstract Objective This study aims to investigate nursing staff’s current knowledge-attitude-practice(KAP) regarding nursing document quality control and to explore effective methods to enhance their awareness of nursing documents’ importance through intensive training. Methods We developed the questionnaire based on a systematic literature review and two rounds of Delphi expert consultation. Then, we sent the questionnaire to the nurses before and after the intensive training.Data processing and statistical analysis were conducted using R 4.4.0 software. Results Altogether, 722, 701, and 800 nurses participated in the questionnaire survey before the training and after two training rounds, respectively. There was no statistically significant difference between the respondents’ baseline data (gender, age, professional title, position, educational background, and working years) before and after the training. After two rounds of intensive quality control training, the nursing staff’s median scores in the knowledge, attitude, and practice dimensions increased from 45 points before the training to 49, 50, and 50 points, respectively, and the difference was statistically significant (P < 0.05). Regression analysis indicated that the longer the working years, the higher the scores of the nursing staff after the training (3–5 years, P < 0.01, 95% Confidence Interval (CI), 0.2–0.57), (6–10 years, P < 0.01, 95% CI, 0.35–0.73), (> 10 years, P = 0.003, 95% CI, 0.32–0.72).The nursing staff with the titles of Chief Nurse (P < 0.01, 95% CI, 0.2–0.54) and Deputy Chief Nurse (P < 0.01, 95% CI, 0.21–0.74) scored higher after the training. Conclusion This study shows that, after two rounds of training, nurses’ KAP of the quality control of nursing documents significantly improved. The training had a positive impact on their KAP, which is conducive to enhancing the quality of nursing documents and nursing care. Therefore, hospitals should emphasize the quality control of nursing documents and take effective measures to help nurses continuously improve the quality of nursing documents.